Hypertension Causes, Impacts, and Control Strategies In The Modern Era - Abdul Thalib (Indonesian Journal of Nursing and Health Care, 2025)
Background: Hypertension, or high blood pressure, is a global health problem that affects about 1.13 billion people worldwide. According to the World Health Organization (WHO), hypertension is a major risk factor for cardiovascular disease, stroke, and premature death. The disease is often asymptomatic, so many individuals are unaware of their condition until serious complications occur. Therefore, a better understanding of the causes, impacts, and control strategies of hypertension is essential.Objective: The aim of this study is to understand the causes, impacts, and control strategies of hypertension in order to reduce its prevalence and improve individuals' quality of life.Methods: This literature review is conducted by collecting and analyzing relevant scientific studies and articles on hypertension. The sources used include medical journals, reports of health organizations, and clinical guidelines published between 2003 and 2024. The literature selection process was carried out using keywords such as "hypertension", "hypertension control", and "hypertension impact" in academic databases such as PubMed (57) and Scopus (279).Results: There were 16 articles that were included in this literature and showed that the factors that cause hypertension include unhealthy lifestyles, genetic factors, and other medical conditions. Significant health impacts of hypertension include an increased risk of heart disease and stroke. Effective control strategies, such as dietary changes, increased physical activity, and the use of antihypertensive medications, have been shown to lower blood pressure.Conclusion: Hypertension is a health problem that requires serious attention. By understanding the causes and impacts of hypertension, as well as implementing effective control strategies, we can reduce the prevalence of hypertension and improve the quality of life of individuals. Collaborative efforts between health workers, governments, and communities are essential to achieve this goal.